2012
DOI: 10.1074/jbc.m112.400911
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Interaction of Interleukin (IL)-32α with Protein Kinase Cϵ (PKCϵ) and STAT3 Protein Augments IL-6 Production in THP-1 Promonocytic Cells

Abstract: Background: IL-32␣ is known to interact with FAK1, and IL-32␣ overexpression in chronic myeloid leukemia cells increases natural killer cell-mediated killing. Results: IL-32␣ interacted with PKC⑀ and STAT3, mediated STAT3 phosphorylation, and thereby augmented IL-6 production. Conclusion: IL-32␣ elevated IL-6 production through interaction with PKC⑀ and STAT3. Significance: The interaction of IL-32␣ with PKC⑀ and STAT3 reveals a new intracellular mediatory role of IL-32␣.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
76
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 50 publications
9
76
0
Order By: Relevance
“…In this study, we solved our previous question by revealing the mechanism by which IL-32␤ promotes IL-10 production. Recently, several studies have shown the intracellular mediatory function of IL-32 (7,8,33). We demonstrated that IL-32␤ mediated the phosphorylation of serine 21 on C/EBP␣ by PMA-activated PKC␦, which resulted in IL-10 production.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In this study, we solved our previous question by revealing the mechanism by which IL-32␤ promotes IL-10 production. Recently, several studies have shown the intracellular mediatory function of IL-32 (7,8,33). We demonstrated that IL-32␤ mediated the phosphorylation of serine 21 on C/EBP␣ by PMA-activated PKC␦, which resulted in IL-10 production.…”
Section: Discussionmentioning
confidence: 82%
“…cDNAs for PKC␣, PKC␦, PKC⑀, and PKC were subcloned into the pcDNA3.1 ϩ 5ϫFLAG vector by using EcoRI and XhoI (7). Human intronless C/EBP␣ gene was PCR-amplified from THP-1 genomic DNA by using two overlapping primer sets to obtain the entire cDNA; PCR was then conducted again using the two-PCR fragment as templates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-32α has been reported as the most abundant transcript and the IL-32γ isoform as the longest transcript with most prominent biological activity [13]. Apart from the proinflammatory role of IL-32, the association of IL-32α with PKCε and STAT3 [14] or with FAK1 has been reported [15], suggesting a possible role of this cytokine as an intracellular signaling mediator. Furthermore, the role of IL-32 in the production of regulatory cytokines has been described: IL-32β interacts with PKCδ and C/EBPα, which results in the production of IL-10 [16], and IL-32γ is correlated with enhanced production of proinflammatory cytokines, such as IL-1β and IL-6 [17].…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of IL-32 decreased TNF-␣, ⌱L-1␤, IL-6, and IL-8 expression in monocytic THP-1 cells and human umbilical cord vein endothelial cells (HUVECs) (26,27). Impressively, upregulation of IL-6 can be enhanced by the interaction between IL-32␣, protein kinase Cε (PKCε), and STAT3 protein in monocytic THP-1 cells (28). In neutrophils, IL-32 can interact with proteinase 3, which may result in the enhancement of IL-32 production to induce IL-8 (29).…”
mentioning
confidence: 99%